2003
DOI: 10.1161/01.atv.0000090672.07568.60
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Artery Structural and Functional Changes During Pregnancy in Tissue Kallikrein–Deficient Mice

Abstract: Objective-Tissue kallikrein (TK) participates in acute flow-induced dilatation (FID) of large arteries. We investigated whether TK deficiency blunts FID and alters chronic flow-related arterial structural and functional changes in resistance-sized muscular arteries. Methods and Results-Vasomotor responses and structural parameters were determined in uterine arteries isolated from nonpregnant, 18-to 19-day pregnant, and 7-day postpartum TK Ϫ/Ϫ and TK ϩ/ϩ littermate mice. In TK Ϫ/Ϫ mice, values of diameter, medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 45 publications
5
46
0
Order By: Relevance
“…In mice, an increase in the lumen diameters of mesenteric arteries was observed only in the PP period, and this was hypothesized to be related to elevated mesenteric blood flow. 12 In our study, we found a residual increased distensibility in the maternal mesenteric arteries of normal mice at 4 weeks PP but not in vessels from immunodeficient mice. Arterial compliance is controlled by multiple mechanisms, including arterial wall collagen-elastin composition, smooth muscle cell plasticity, and may involve molecules such as relaxin, 76 matrix metalloproteinases, 64 sex steroids, 77 fibulin, 78 angiotensin, and NO, among others.…”
Section: Discussionsupporting
confidence: 40%
“…In mice, an increase in the lumen diameters of mesenteric arteries was observed only in the PP period, and this was hypothesized to be related to elevated mesenteric blood flow. 12 In our study, we found a residual increased distensibility in the maternal mesenteric arteries of normal mice at 4 weeks PP but not in vessels from immunodeficient mice. Arterial compliance is controlled by multiple mechanisms, including arterial wall collagen-elastin composition, smooth muscle cell plasticity, and may involve molecules such as relaxin, 76 matrix metalloproteinases, 64 sex steroids, 77 fibulin, 78 angiotensin, and NO, among others.…”
Section: Discussionsupporting
confidence: 40%
“…The characteristics of the uterine artery waveform in the mouse were similar to that of the human, despite their much higher heart rate (ϳ500 beats/min in mice vs. ϳ75 beats/min in humans) and their much smaller uterine artery diameter (0.46 mm in mice vs. 3.4 mm in humans) (23,43). In both species, the nonpregnant uterine artery waveform has a prominent diastolic notch and a high resistance index of 0.7, although the peak systolic velocity of 23 cm/s in the mouse tends to be lower than the 32 cm/s velocity observed in humans (Table 1).…”
Section: Discussionmentioning
confidence: 89%
“…Local arteriolar and ascending vasodilatation results in an increased blood flow through the upstream resistance arteries. The resulting increase in wall shear stress triggers release of endothelium-derived vasodilators, such as nitric oxide (NO), prostacyclin, bradykinin, and endothelium-derived hyperpolarizing factor (22,24). The increase in luminal diameter tends to restore wall shear stress and leads, together with the increase in transmural pressure, to an elevation of circumferential wall stress and of the strain on the resistance arterial smooth muscle cells (SMC).…”
Section: Flow-induced Vasodilatation and Flow-induced Remodeling Of Rmentioning
confidence: 99%
“…Angiogenesis, estrogeninduced upregulation of endothelial NOS, vasodilatation, and remodeling of spiral arteries and uterine arteries contribute to the increased blood flow to the growing uterus and fetuses (5). The luminal diameter and media mass of uterine arteries increase markedly in pregnant mice (22,23). This increase is accompanied by dedifferentiation of the SMC (19).…”
Section: Physiological Flow-induced Resistance Artery Remodelingmentioning
confidence: 99%
See 1 more Smart Citation